Experimental investigation of Euler’s elastica: in-situ SEM nanowire post-buckling - Aleksandra Manecka-Padaż; Piotr Jenczyk; Ryszard B. Pęcherski; Anna Nykiel (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2022)
An in-situ nanoindenter with a flat tip was employed to conduct buckling tests of a single nanowire with simultaneous SEM imaging. A series of SEM images allowed us to calculate deflection. The deflection was confronted with the mathematical model of elastica. The post-buckling behaviour of nanowires is conducted in the framework of the nonlinear elasticity theory. Results show the significant effect of geometrical parameters on the stability of buckled nanowires.